2011
DOI: 10.1371/journal.pone.0020348
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Stress Regulates the Invasive Potential of Glioma Cells via Modulation of Migratory Activity and Matrix Metalloproteinase Expression

Abstract: BackgroundGlioma cells are exposed to elevated interstitial fluid flow during the onset of angiogenesis, at the tumor periphery while invading normal parenchyma, within white matter tracts, and during vascular normalization therapy. Glioma cell lines that have been exposed to fluid flow forces in vivo have much lower invasive potentials than in vitro cell motility assays without flow would indicate.Methodology/Principal FindingsA 3D Modified Boyden chamber (Darcy flow through collagen/cell suspension) model wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(147 citation statements)
references
References 53 publications
(101 reference statements)
7
140
0
Order By: Relevance
“…Interstitial flow has been implicated in modulating several cell functions including transport function in the lymphatic endothelium (33), fibroblast alignment, migration, and TGF-b activation (34). A recent report examined the effect of shear flow on glioma cells and found that invasion decreased (35). However, this study primed the cells with acute flow followed by exposure to stable chemokine gradients and was interested in only the cells migrating after this flow period (under static conditions).…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial flow has been implicated in modulating several cell functions including transport function in the lymphatic endothelium (33), fibroblast alignment, migration, and TGF-b activation (34). A recent report examined the effect of shear flow on glioma cells and found that invasion decreased (35). However, this study primed the cells with acute flow followed by exposure to stable chemokine gradients and was interested in only the cells migrating after this flow period (under static conditions).…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial flow is driven by hydrostatic and osmotic pressure gradients that exist between arterioles, the interstitial space, lymphatic capillaries, and post-capillary venules, 15 and fluid flow between the blood to the lymphatics can be dramatically increased under pathological conditions such as inflammation and cancer. 14,16,17 Interstitial flow has been hypothesized to affect cell migration in a number of different ways, including matrix stiffening and local strain gradient induction, [18][19][20][21] flow-upregulated proteolysis by migrating cells, 3,22 stress-mediated cytokine activation, 23 and autologous chemotaxis. [23][24][25] In the latter mechanism, autologously secreted (or activated) chemokine forms local pericellular diffusion gradients skewed by fluid convection, and the cells subsequently ''chemotact'' up the flow-directed gradient; this requires that the migrating cell expresses both the chemokine to which it is chemotactically sensitive as well as its receptor, such as CCL19/ CCR7 by dendritic cells 26 and some types of invasive tumor cells.…”
Section: Insight Innovation Integrationmentioning
confidence: 99%
“…3E, left). 22,24 To do this, we first carried out experiments with two different average flow velocities (limited by technical considerations), 0.4 and 4 mm s…”
Section: Interstitial Flow Increases the Migrational Population And Smentioning
confidence: 99%
“…At the same time, in vitro models cannot recapitulate every aspect of the tumor microenvironment, and thus care must be taken to identify their limitations and assumptions. For example, while a threedimensional (3D) culture of tumor cells in a collagen gel under interstitial flow might be used to explore direct effects of interstitial flow on tumor cell invasion [23][24][25], it ignores other factors present at an invasive edge of the tumor such as the architecture and composition of the ECM (which is highly heterogeneous), the diversity of cell types present in the tumor stroma and their physiological interactions, and gradients of oxygen, pH, metabolites, and nutrient that are formed from the tumor mass. As such, one can only infer from such studies the direct effects of interstitial flow on uniformly distributed tumor cells within a homogeneous collagen ECM (which itself is important), but not necessarily translate those findings directly to the tumor invasive edge, since one does not know the relative importance of interstitial flow versus the other factors that were excluded from the in vitro model.…”
Section: Introductionmentioning
confidence: 99%